Evaluation of Blood Lactate, Heart Rate, Blood Pressure, and Shock Index, and Their Association with Prognosis in Calves - Hélène Casalta; Calixte Bayrou; Salem Djebala; Justine Eppe; Linde Gille; Kris Gommeren; Eva Marduel; Arnaud Sartelet; Celine Seys; Jérôme Versyp; Sigrid Grulke (Veterinary Sciences, 2024)
Diseases in young calves received as emergencies are often associated with hypovolemic and/or septic shocks. The objectives of our study were to (1) assess the correlation between clinical hemodynamic parameters and blood L-lactates (LAC), systolic blood pressure (SBP), and the shock index (SI) recorded upon arrival; and (2) to evaluate how these parameters were related to short-term outcomes in calves under 4 months of age presented as emergencies. We conducted a single-observer prospective observational study on calves aged from 1 day to 4 months, presented to the Veterinary Clinic for Ruminants of Liège from December 2020 to May 2022. Forty-five calves were included in the study. The statistical analysis revealed a significant correlation between LAC and heart rate (r = 0.570; p < 0.05) and LAC and SI (r = 0.373; p < 0.05). A high LAC value at admission was significantly associated with a negative outcome (death) (p < 0.05). In calves suffering from obstructive digestive diseases, the SI was related to the outcome and the analysis indicated a cut-off value of 1.13 (Se = 0.77, Spe = 1). In conclusion, in our study, the initial blood L-lactate value was correlated with heart rate, the shock index, and the clinical shock score, and admission hyperlactatemia was associated with a poor prognosis in calves under 4 months of age. In this cohort, the shock index in calves suffering from digestive diseases was linked with mortality.